Mandibular Condyle Shape and Symmetry in 4- to 19-Year-Old Children and Early Adolescents - Bonardo, Barnabas; Saskianti , Tania; Moeharyono Puteri, Mega (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background: The prevalence of TMD (temporomandibular disorder) in children and early adolescents varies widely. TMD can cause permanent facial deformities and affect occlusion and speech, which will affect growth, development, and quality of life. For prevention, early detection is needed. However, early detection is often not possible due to a lack of understanding of the normal shape of the condyle. Research on the normal shape of the condyle and symmetry in children and early adolescents has not been much done. Purpose: To evaluate the shape of normal condyles in a population of children and early adolescents aged 4–19 years and determine the most dominant shape and symmetry. Methods: 220 mandibular condyles of 110 children aged 4–19 years (mean 11.4 years) were analyzed retrospectively using an orthopantomograph. Condyle types in primary, mixed, and permanent dentition were categorized according to Yale (convex, rounded, flat, angled) and Chaudhry classification (oval, diamond, bird beak, crooked). Right and left mandibular condyle symmetry was observed according to a previous study by Ribeiro. Results: In primary, mixed, and permanent dentition, the most dominant condyle shapes were (Yale, Chaudhry): 91.6% rounded, 100% oval; 95.8% rounded, 97.9% oval; 98% rounded, 97% oval, respectively. Asymmetry in the right and left mandibular condyles was not found in primary dentition; there were 2 cases in mixed dentition and 3 cases in permanent dentition. Conclusion: In children and early adolescents aged 4–19 years, the normal condyles found are: rounded, convex, angled (Yale), and oval, diamond, or bird beak (Chaudhry). The condyles are dominated by rounded and oval shapes. The incidence of asymmetry in the right and left mandibular condyles probably increases with age.